P34 Successful introduction of an outpatient parenteral antimicrobial therapy (opat) programme in a large uk paediatric hospital. Issue 2 (19th January 2018) - Crouch, Claire; Sharpe, David; Porter, David; Paulus, Stephane
Abstract : Introduction: An OPAT service was launched at large paediatric hospital in November 2014 to facilitate the safe and efficient discharge of patients from hospital into the community. The OPAT service is delivered by a multi-disciplinary team including a Consultant in Paediatric Infectious Diseases, an OPAT/Intravascular Access Nurse, an Antimicrobial Pharmacist, and involves collaborative working with community nursing teams across the region. We present an evaluation of our service based on audit data and patient feedback collected over a 12 month period. Methods: Prospective audit using the BSAC p-OPAT (British Society of Antimicrobial Chemotherapy Paediatric Out-patient Parenteral Antimicrobial Therapy) database including data from 1 st January 2015 to 31 st December 2015. Results: Two hundred and thirteen patients were admitted to the OPAT service leading to 1749 bed-days saved for the trust. Seventy-four patients avoided admission. The most common conditions were: bronchiectasis/chronic respiratory tract infection (15.5%), bacteraemia (15%), pre-septal cellulitis (15%) and respiratory tract infection (11.2%). Complex infections were less common but they accounted for longer antibiotic courses, such as cerebral abscess (5 patients – 170 days of intravenous therapy) and endocarditis (3 patients – 75 days of intravenous therapy).Using the BSAC outcomes definitions, we reported a 90% infection cure rate with a further 6.5% showing clinical improvement. OPAT outcomes were: success in 87% and partial success in 8.5%. The remaining patients (n=6) were classified as OPAT failures due to worsening of infection, drug reactions or inability to re-establish lost vascular access.Feedback from children and parents showed overall satisfaction with the OPAT service. Completed feedback questionnaires (n=30) rated the support and care as satisfactory or better in all cases, with over 83% rating the service as excellent. Conclusion: We report a positive financial and clinical impact of a new paediatric OPAT service. The service expansion will focus on the involvement of new patient groups (oncology, general surgery) and the increase use of elastomeric devices allowing for an increase number of patients to be treated in their home environment.